A Tríade Social e suas implicações para a teologia bíblica veterotestamentária. Indícios de uma teologia marginal - Lage, Jovanir (2021)
The present work exposes the interest in a social reading of the Old Testament and seeks to develop it, analyzing a considerable system of laws that foresees the physical and social aspects of individuals in vulnerable situations. The sociological criteria, developed here, seek to distinguish from institutionalized religion, an invisible and marginal religion, with deep anthropological and social roots. At the center of this system that shelters the marginalized of society, we find the Social Triad: foreigner rGEï, orphan ~At±y" and widow hn"ôm'l.a". The objective of our research is to analyze the presence of these categories in the text biblical and how they point to a significant set of legal norms, produced by groups opposing the “official religion”, developing totally new conceptions in the theological, political and cultural fields. The method found to investigate our suspicions is in the exegetical study of biblical texts , in particular, Deuteronomic texts and extra-biblical texts, supported by the archaeological finds in Khirbet Qeiyafa. The preliminary results of our research give us clues that the social practice, very widespread in ancient Israel, understood as a divine requirement, reaches liturgical contours important in establishing ethical and social values in the community. Our intention is to emphasize that the theme of the poor and needy, represented and n our research into the Social Triad, as well as the preservation of its basic rights, permeates the entire Old Testament, promoting a kind of marginal theology, which runs parallel to the official themes and dynamics of faith.